Skills-specific competitive timeframes in rugby sport - Kokoulina, O. P.; Tatarova, S. Yu.; Averyasov, V. V.; KruglovaYu. V. (Theory and Practice of Physical Culture, 2018)
The study analyzes the skill-specific competitive performance timing data in modern rugby, with the external parameters of the game process including the total and net game times in competitions of different levels. The study also considers the internal time structure of the game process versus the technical and tactical intensity of the game moments and players` skill levels in the competitive matches. The skills-specific study data for a comparative analysis were obtained from the match records. The study data and analyses give the means to conclude that higher skills, formal qualifications and actual mastery levels result in wider variations of competitive performance time elements including total game time, elementary game moments and game service intervals. In this context the competitive performance is recommended to be designed with the above elements being duly taken into account and harmonized. The study data show the need for the athletes` mastery and competitive progress being secured by an integrated training process designed as required for the competitive success.